Association between contralateral adrenal and hypothalamus-pituitary-adrenal axis in benign adrenocortical tumors - Zhu, Hongyuan; Wu, Luming; Su, Tingwei; Jiang, Lei; Zhou, Weiwei; Jiang, Yiran; Zhang, Cui; Zhong, Xu; Wang, Weiqing (Frontiers in Endocrinology, 2023)
Context: Adrenal incidentaloma (AI) is commonly discovered on cross-sectional imaging. Mild aAutonomous cortisol secretion (mild and definitive) are the most common functional disorder detected in AI.Objective: To delineate the association between radiological characteristics of benign adrenocortical tumor and hypothalamus-pituitary-adrenal (HPA) axis.Methods: In the study, 494 patients diagnosed with benign unilateral adrenocortical tumor were included. Mild autonomous cortisol secretion (MACS) was diagnosed when cortisol after 1mg-dexamethasone suppression test (1-mg DST) was in the range of 1.8-5ug/dl. Nonfunctional adrenocortical tumor (NFAT) was diagnosed as cortisol following 1-mg DST less than 1.8ug/dL. We performed Logistics regression and causal mediation analysis for associations between radiological characteristics and HPA axis.Of 494 patients, 352 (71.3%) with NFAT, 142 (28.7%) with MACS were included. Patients with MACS had higher tumor diameter, thinner contralateral adrenal gland and lower plasma ACTH, serum DHEAS than those with NFAT. ACTH (OR 0.978, 0.962-0.993) and tumor diameter (OR 1.857, 95%CI, were independent factors associated with decreased serum DHEAS (all P<0.05). ACTH was also associated with decreased contralateral adrenal diameter significantly (OR 0.973, 95%CI, 0.957-0.988, P=0.001). Causal mediation analysis showed ACTH mediated the effect significantly for association between 1-mg DST results and DHEAS level (Pmediation<0.001, proportion=22.3%). Meanwhile, we found ACTH mediated 39.7% of the effects of 1-mg DST on contralateral adrenal diameter (Pmediation=0.012).Patients with MACS had thinner contralateral adrenal gland and 3 disturbed HPA axis compared with NFAT. ACTH may partially involve in mediating the mild autonomous cortisol secretion to DHEAS and contralateral adrenal gland.